TRANSESTERIFICATION AND AMIDATION REACTION OF ERUCA SATIVA SEED OIL - Salieva , Gulrukh; Kholiqov , Tursunali; Matchanov , Alimjan (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
Eruca sativa refers to the family Brassicaceae, which includes a large number of plant species and is used for various purposes such as food and medicine. In the present study, Transesterification and amidation reaction of Eruca sativa seed oil was carried out and analyzed by TLC and IR Spectroscopy.